FIRST LANGUAGE ACQUISITION IN LATE TALKING TODDLERS - Widya, Pratiwi Rizky (Institut Agama Islam Negeri Palopo, 2017)
This paper is aimed at describing Development Language Delay (DLD) or Late Talking (LT) toddler from the perspective of a normally developing toddler. This study examined when children are identified as normal development or late talking toddlers, characteristics of late talking toddlers, factors influence late taking toddler and how to help children in their language development. The study focused at 2-year-olds with a vocabulary delay whose nonverbal cognitive abilities fell within the normal range for their chronological age. Late talking toddler is a toddler who has a good understanding of language, typically developing play skills, motor skills, thinking skills, and social skills, but has a limited spoken vocabulary for his or her age. Although late talking only limited to speech delay, but it does not receive proper medical treatment/ therapy/ intervention, there will be other disturbances follow it, e.g., disturbances in behavior, psychosocial disorders, poor academic ability, and so on.